السمات الجيومورفولوجية والمورفومترية للأودية الموسمية في منطقة السبلوقة - شمال الخرطوم السودان (Journal of Faculty of Education, 2021)
Research done on Sabaloka area (latitudes 160 12/, and 160 24/ N., and longitudes 330 and 330 36/ E) focused more on its geology rather than on its geomorphology, and particularly the seasonal wadis in the area. The authors consider that, understanding the geomorphological and morphometrical characteristics of these seasonal wadis is important for better understanding of its geomorphology, the influence of paleoclimate and for future utilization. The objective of this research is to identify the geomorphological and morphometrical characteristics of the seasonal wadis of Sabaloka area and to discuss the influence of major physical factors, particularly paleoclimate, on determining the nature and origin of these wadis. Methods of data collection included field works during 1996 and 1997, field trips between 2010 and 2014, and analysis of satellite images for the years 1983 and 2014, to determine the in particular the morphometric and topographic characteristics.. اًاThe main analysis revealed that seasonal wadis of the study area can be divided geographically into eastern wadis and western wadis based on the area’s topography, water divides and slope towards the River Nile. The Eastern wadis exhibit differences in depth, type,, shape, and size of deposits whereas in the western wadis,differences are confined to the shape and size of the deposits.In general, all these wadis have contributed to the formation of the flood plain of the Nile because they usually transport clayey, sandy and gravelly deposits. The main channels of the seasonal wadis reveal parallel and dendritic patterns of drainage which are characteristic in the upper reaches of Abu Gadad valley and the middle channel of Abu Gaduiem valley, and the radial pattern in Musa, Shuluk, and Sada wadis which drain the volcanic plateau . Morphometrical analysis of Abu Gaidoum and Abu Gadad wadis revealed that Abu Gaidoum is more developed than Abu Gadad, and morphometrical differences between these two wadis could be attributed to area factor. The research arrived at the conclusion that seasonal wadis of Sabaloka area could be considered as part of the paleo drainage systems of the River Nile, the Sahara and Red Sea Hills, and that paleoclimate and geological structure have significantly determined the geomorphological and morphometrical characteristics of these wadis and the differences between them.
Keywords: السبلوقة; الساحل الأفريقي; وحدة جيومورفولوجية; تعرية هوائية; تجوية ميكانيكية; جبال انعزالية; البيدمنت; مناخ قديم